The Space Physics Environment Data Analysis System in Python - Grimes, Eric W.; Harter, Bryan; Hatzigeorgiu, Nick; Drozdov, Alexander; Lewis, James W.; Angelopoulos, Vassilis; Cao, Xin; Chu, Xiangning; Hori, Tomo; Matsuda, Shoya; Jun, Chae-Woo; Nakamura, Satoko; et al. (Frontiers in Astronomy and Space Sciences, 2022)
In this article, we describe the free, open-source Python-based Space Physics Environment Data Analysis System (PySPEDAS), a platform for multi-mission, multi-instrument retrieval, analysis, and visualization of Heliophysics data. PySPEDAS currently contains load routines for data from 23 space missions, as well as a variety of data from ground-based observatories. The load routines are built from a common set of general routines that provide access to datasets in different ways (e.g., downloading and caching CDF files or accessing data hosted on web services), making the process of adding additional datasets simple. In addition to load routines, PySPEDAS contains numerous analysis tools for working with the dataset once it is loaded. We describe how these load routines and analysis tools are built by utilizing other free, open-source Python projects (e.g., PyTplot, cdflib, hapiclient, etc) to make tools for space and solar physicists that are extremely powerful, yet easy-to-use. After discussing the code in detail, we show numerous examples of PySPEDAS, and discuss limitations and future plans.